HYDROXYAPATITE COATING BY MECHANICAL ALLOYING METHOD - Hannora, A.; Aknazarov, S.; Mansurov, Z.; Mofa, N.; Mamaeva, A. (Recent Contributions to Physics, 2009)
Hydroxyapatite [Ca10(PO4)6(OH)2 - HA] material has been clinically applied in many areas of dentistry and orthopaedics. Presented work describes the effect of mechanical alloying treatment, as a nonconventional solid-state process, on the microstructure of hydroxylapatite powder and Ti- alloy substrate. The relationship between the crystallinity, crystallite size and strain of the HA with milling factors was investigated. Milled HA powders and Ti-substrate were characterized by X-Ray Diffraction (XRD) and/or scanning probe microscope (SPM) using atomic force microscopy (AFM). Increasing the ratio of the weight of the ball to the powder (Wb:Wp) ratio and milling time accelerates the broadening and intensity reduction of XRD peaks. There was no evidence that milling time up to 2h or Wb:Wp can change chemical composition of the HA. Decomposition of HA phase or secondary phases such as α and/or β-tri-calcium phosphate (α, β - TCP), and calcium oxide (CaO) was not observed throughout the milling process. The average grain size and the internal strain are calculated from the XRD by Scherrer’s formula and Hall–Williamson method. The Ti doped HA samples shows a notable broadening and intensity reduction comparing with HA powders before and after milling.